Macrophage–glia interactions regulate immune damage to enteric neurons during West Nile virus infection - Hana Janova; Fang R. Zhao; Ali Akgul; Meredith Schatz; Daniel M. Alligood; David M. Alvarado; Larissa B. Thackray; Thaddeus S. Stappenbeck; Michael S. Diamond (Proceedings of the National Academy of Sciences, 2026)
Functional gastrointestinal (GI) tract disorders affect a substantial proportion of the global population and are often preceded by intestinal infections that cause injury to enteric neurons and glia through unrestrained immune responses. However, the mechanisms that limit infection-induced inflammation and protect the enteric nervous system remain poorly understood. Here, we defined such neuron–glia–macrophage interactions after West Nile virus (WNV) infection; this model neurotropic virus causes GI tract dysmotility in mice via injury of enteric neurons through a T cell–mediated cytolytic mechanism. In response to WNV infection, RNA sequencing analysis showed that resident muscularis macrophages upregulate antiviral, proinflammatory, and immunomodulatory genes. Whereas pharmacological depletion of resident macrophages did not affect the viral burden in the GI tract, it instead reshaped the enteric glial response to WNV, resulting in excessive production of T cell and neutrophil chemoattractants. The amplified recruitment of these immune cell types worsened enteric neuronal injury. Together, our findings identify resident muscularis macrophages as key regulators of glia-driven inflammation during enteric viral infection and reveal their role in protecting enteric neurons from immune-mediated damage.